The teaching readiness of pre-service teachers from the economics and business education programs - Siswanto Siswanto; Ali Muhson; Rosidah Rosidah; Eka Ary Wibawa (LPMPP Universitas Negeri Yogyakarta, 2022)
This study aims to examine the teaching readiness level of pre-service teachers from the Economics Education, Accounting Education, and Office Administration Education study programs and the discrepancy between them. Ex post facto research design was applied in this study with quantitative approach. Pre-service teachers from educational study programs in the Faculty of Economics Universitas Negeri Yogyakarta that have completed micro teaching and educational practice courses were involved as the population in the present study. A total of 262 pre-service teachers were selected as the samples using purposive random sampling method. A questionnaire was used to collect the data. The instrument validity was confirmed using exploratory factor analysis, while the reliability was estimated using Cronbach Alpha. The data were analyzed statistically using descriptive quantitative and Multivariate Analysis of Variance (MANOVA). The result showed that the teaching readiness of the pre-service teachers from the Economic Education, Accounting Education, and Office Administration Education study programs were in the “excellent” category, and no significant differences were found on their teaching readiness level. The results indicated that each study program showed a similar performance in providing the pre-service teachers with an appropriate level of teaching readiness. Grounded on the research results, it is suggested to maintain the schooling pattern for all educational study programs for an in-depth study in the future with different characteristics of each study program.